(untitled) (Research, Society and Development, 2022)
Methodology: This article, with a cross-sectional design, in 2020, between january and december, and was carried out through an interview in the municipality of Jaraguari-MS,aiming at the understanding and applicability of spiritual intelligence in the Community of Furnas do Dionísio. Furthermore, the phenomenological profile was used to analyze the interviews. Objective: Reflection on the application and development of spiritual intelligence in the community of Furnas do Dionísio. Results: It was finally possible to notice that the interviewed participants from the community in question have a high level of spiritual intelligence, based on the analyzed data. Conclusions: The relevance of this text is clear, as expected by the authors, the participants of the Furnas do Dionísio Community presented a high level of spiritual intelligence, however, due to the pandemic situation, this article could not have a larger sample, needing, therefore, future research that can complement it and increase the bibliographic collection on the subject in question.